Perancangan Aplikasi PPDB (Penerimaan Peserta Didik Baru) Pada Sekolah Dasar Negeri Buaran 01 Berbasis Web Menggunakan Metode Waterfall - Ihsan Fauzi, Muhammad; Jaya Giri Pratama, Donny; Saprudin (BINER : Jurnal Ilmu Komputer, Teknik dan Multimedia, 2024)
This study designs a web-based application for New Student Admissions (PPDB) at SD Negeri Buaran 01 using a qualitative descriptive method. The goal is to automate the registration process, manage prospective student data, and provide PPDB-related information, which were previously handled manually. The research stages include problem identification, literature review, data collection through observation and interviews, data analysis, application design, testing, and evaluation. The developed application features online registration, prospective student data management, announcement notifications, and reporting. The result is an application that enhances operational efficiency, facilitates the registration process, and supports faster, more accurate decision-making.